Processing Household Waste into Organic Compost Fertilizer to Overcome Environmental Pollution in Lok Rawa Village, Barito Kuala Regency - Emma Ruhaidani; Irwandy Muzaidi; Ichwan Setiawan (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
The problem of waste in Lok Rawa Village so far has not been completely solved, apart from the absence of a garbage collection site in the village, public awareness of not littering is still very low. In addition, there is still a lack of knowledge about how to treat household waste. One solution or alternative that is efficient is waste processing by sorting organic waste produced by local residents and processing it into compost. With this activity, the people of Lok Rawa village know the negative impact of using inorganic fertilizers, namely the occurrence of soil pollution. The community also knows the benefits of using organic fertilizers, one of which is compost from household waste, which can help the community's economy and also help overcome environmental pollution. In addition, the composting program also provides knowledge to the community to manage household waste into compost independently.